Formulation Development and Evaluation of Drug Loaded Microsponges of Sulindac Sodium - Pethappachetty, Palanisamy; Chandira, Rajappa Margret; Kumaresan, Karthir; samy, Dominic Antony (Asian Journal of Biological and Life Sciences)
This research work aimed to develop and evaluate the microsponge formulations for Sulindac sodium. Sulindac sodium a poorly water-soluble drug with high first-pass metabolism is available only as conventional tablets. Thus, an attempt was made to formulate a drug-loaded microsponge to eliminate the first-pass metabolism and also improve the bio-availability of the drug. This work aimed to prepare a stable microsponge formulation of sulindac sodium for the enhancement of bioavailability and reducing the dose frequency. The quasi emulsion solvent diffusion approach was used to create the microsponges. The percentage yield, drug load efficiency, morphological analysis, in vitro drug release and stability studies were evaluated. Based on the result selected for the optimized formulation SM5, the morphology of the optimized formulation was by scanned electron microscopy which was found to be uniform and containing pores without any crystals. The formulation SM5 was found to be in an optimized formulation which shows 92.05% release at 12 hr. Stability studies showed that indicated negligible levels of changes were observed in load efficiency, morphological analysis and in vitro release, indicating the susceptibility to stability problems during storage at room temperature and 40°C/75%RH was observed after 3 months. On the basis of the findings, drug-loaded microsponges show improvised release behaviour and provide an effective modified route of administration.
Keywords: Microsponge; morphological analysis and in vitro drug release; Porous polymeric system; Solubility; Sulindac sodium